1966
DOI: 10.1002/1520-6807(196607)3:3<208::aid-pits2310030305>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Graduation from high school as predicted from the California psychological inventory

Abstract: 1964) has recently published a textbook that could well serve as a tremendously practical handbook for the teacher, and help to make him much more efficient at his teaching task if he were to make daily use of the principles it enumerates. Yet, few teachers will probably ever read this little book because behavioristic psychology and humanistic education have little in common in the eyes of the teacher educator as well as the practicing teacher. It is hoped that the present discussion has helped to clarify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…However, GED recipients have noncognitive skills (personality traits) similar to high school dropouts. 183 Supporting the evidence from the GED program that personality plays an important role in explaining educational attainment in adolescence, several prospective studies have shown that facets of Conscientiousness (e.g., self-control, distractibility) and facets of Neuroticism (e.g., internal locus of control) predict successful graduation from high school (Bowman and Matthews [1960;Gough [1964;Hathaway, Reynolds and Monachesi [1969;Janosz, LeBlanc, Boulerice et al [1997;Kelly and Veldman [1964;Whisenton and Lorre [1970]). 184 Table 9 presents findings from three more recent studies examining the relationship between locus of control, a trait related to Emotional Stability, and high school graduation.…”
Section: Educational Attainmentmentioning
confidence: 98%
“…However, GED recipients have noncognitive skills (personality traits) similar to high school dropouts. 183 Supporting the evidence from the GED program that personality plays an important role in explaining educational attainment in adolescence, several prospective studies have shown that facets of Conscientiousness (e.g., self-control, distractibility) and facets of Neuroticism (e.g., internal locus of control) predict successful graduation from high school (Bowman and Matthews [1960;Gough [1964;Hathaway, Reynolds and Monachesi [1969;Janosz, LeBlanc, Boulerice et al [1997;Kelly and Veldman [1964;Whisenton and Lorre [1970]). 184 Table 9 presents findings from three more recent studies examining the relationship between locus of control, a trait related to Emotional Stability, and high school graduation.…”
Section: Educational Attainmentmentioning
confidence: 98%
“…internal locus of control) predict successful graduation from high school (Bowman and Matthews [1960;Gough [1964;Hathaway, Reynolds and Monachesi [1969;Janosz, LeBlanc, Boulerice et al [1997;Kelly and Veldman [1964;Whisenton and Lorre [1970]). 181 Table 9 presents findings from three more recent studies examining the relationship between locus of control, a trait related to Emotional Stability, and high school graduation.…”
Section: Educational Attainmentmentioning
confidence: 99%
“…The 23 adjustment scale items in the CPI (Gough, 1966(Gough, , 1996(Gough, , 2000 assessed the extent to which the participant feels she is managing life well. Respondents indicated whether they agreed or disagreed with each item.…”
Section: Instruments Time 1 Measurement (Pre-intervention)mentioning
confidence: 99%